Optimization of fermentation process of papaya sauerkraut using response surface method - Lijuan, Zhang; Jinsong, Yang; Liwei, Ma; Haisheng, Tan (International Journal of Agricultural and Biological Engineering, 2014)
Papaya, a tropical fruit was used as the raw material to produce sauerkraut in the study. Three lactic acid bacteria strains isolated from papaya were added to the sauerkraut to facilitate the fermentation of papaya sauerkraut. In the fermentation process, the dynamic changes of total acid in sauerkrauts at different levels of sugar concentration, salt concentration, inoculation and temperature were studied. The response surface method was used to study the effects of changes in multiple factors at the same time. On the basis of “one-variable-at-a-time” approach, the response surface method optimized papaya sauerkraut fermentation process. According to the change of total acid in single factor, 29 experiments were designed by 4×3 factorial central composite design. The optimum fermentation conditions were obtained as follows: sugar at 3.8%, salt at 2.8%, inoculation at 5%, and temperature at 31℃.Keywords: papaya, sauerkraut, fermentation process, response surface method, lactic acid bacteria, central composite designDOI: 10.3965/j.ijabe.20140703.012Citation: Zhang L J, Yang J S, Ma L W, Tan H S. Optimization of fermentation process of papaya sauerkraut using response surface methodology. Int J Agric & Biol Eng, 2014; 7(3): 102－106.